NEOMONDIALIST PROJECT OF F.FUKUYAMA - Meteleva, E.A (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
Neoliberal ideology today is the leading geopolitical doctrine of the United States, building a long-term strategy of the new world order. F. Fukuyama's neomondialism is a program project on the organization of the modeling process of liberal democracy. The strategic success of the neomondialist program is aimed at the ideas of equality and freedom in the planetary integration of all states and peoples. F. Fukuyama sees the main obstacle to the implementation of the social strategy in the viciousness of religious principles (above all, Christianity) and their distribution on a global scale. On the agenda in the neomondialist project is the question of the destruction of religion. However, the lack of use of knowledge in religious theoretical content does not allow F. Fukuyama to state the main criteria of understanding in the practical implementation of religious culture. The principle of conscience in religious consciousness is a cardinal imperative that impedes the anti-human geopolitical alternatives to the ideology of neoliberalism. The transformation of "The End of History" into a new round of weapons and the widespread unleashing of local wars is in keeping with the geopolitical projects of the politics of realism. In the modern period there is a new position of F. Fukuyama: he is removed from the claims of the neo-conservative worldview and moves to the position of searching for flexible social and political criteria that meet the principles of modernization and humanism.